Rare cases of nasal mass with bleeding: case series - Tanthry, Deepalakshmi; Perdoor, Panchami Shridhar; Santhraya, Mahesh; Pannen, Devan Poothatta; Bhandary, Rukma; Pai, Vishwas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
A thorough evaluation of nasal masses along with early management of the disease can prevent complications and further deterioration of the disease to a larger extent. Nasal mass occurring in the nose with symptoms of epistaxis is a sign of suspicion of malignancy. Patients can have variable presentations according to the site and extent of the infection. This article comprises of study done on 3 patients who presented to the ear, nose, and throat (ENT) out patient department with nasal mass with bleed. All three of the patients were subjected to clinical examination, diagnostic nasal endoscopy, radiological evaluation, surgical intervention and histopathological assessment. Thorough evaluation helps the operating surgeon to come to a specific diagnosis so that the chances of diagnosing rare cases does not get ruled out and helps the further deterioration of the disease.